2011
DOI: 10.1378/chest.10-2471
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Airway Purines in COPD

Abstract: Purinergic signaling pathways regulate airways defense mechanisms, including mucociliary clearance and infl ammatory responses. These pathways are activated by extracellular purines, which include adenosine triphosphate (ATP) and its metabolites adenosine diphosphate, adenosine monophosphate (AMP), and adenosine. Adenosine, in particular, has been linked to infl ammatory airways diseases, 1 including twofold to fourfold elevations in blood 2,3 and BAL fl uid 4 of subjects with asthma. Similarly, adenosine conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 35 publications
3
43
2
2
Order By: Relevance
“…MS methods similar to those used in this study have been used to assess EBC as a noninvasive airway sample. 14,20,38 However, although biomarkers such as AMP function similarly in BALF and EBC, 4,38 the relationships between infl ammation and adenosine and phenylalanine in the current study diff er from previous observations in EBC. 14,20,38 Th us, EBC and BALF may diff er in the metabolites that function optimally as biomarkers, perhaps refl ecting diff erent sites of origin of the airway secretions, 39,40 and further study will be needed to identify the most eff ective metabolomic biomarkers for noninvasive detection.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…MS methods similar to those used in this study have been used to assess EBC as a noninvasive airway sample. 14,20,38 However, although biomarkers such as AMP function similarly in BALF and EBC, 4,38 the relationships between infl ammation and adenosine and phenylalanine in the current study diff er from previous observations in EBC. 14,20,38 Th us, EBC and BALF may diff er in the metabolites that function optimally as biomarkers, perhaps refl ecting diff erent sites of origin of the airway secretions, 39,40 and further study will be needed to identify the most eff ective metabolomic biomarkers for noninvasive detection.…”
Section: Discussioncontrasting
confidence: 80%
“…Chromatographic conditions similar to those of the metabolomics (UPLC BEH C18 column, acetonitrile/formic acid gradients) and previous work (UPLC T3 HSS C18 column, methanol/formic acid gradients 13 ) were explored, with the T3 column judged superior and used for validation. Validation BALF samples were spiked with isotopically labeled internal standard 14 and were fi ltered through a 10-kDa-size selection fi lter (EMD Millipore). Biomarker signals were defi ned as ratios to the internal standard with the closest column run time.…”
Section: Subjects and Samplesmentioning
confidence: 99%
“…However, these results differed from our exhaled breath condensate (EBC) data from subjects with COPD that showed raised ADO levels (49). Induced sputum is believed to originate from large airways, whereas EBC is thought to originate from the small airways of the peripheral lung (25,50,51).…”
Section: Original Articlecontrasting
confidence: 74%
“…24,25 It is also well-documented from lung tissue and bronchial fluid samples that purinergic markers, especially CD73, are elevated in the presence of COPD and hypoxia, 26,27 and in in vivo animal studies demonstrating the effects of CD73 in hypoxia transduction. 17 In the present study, the same effects were observed in blood samples from patients with PAD.…”
Section: Discussionmentioning
confidence: 99%